The Assessment of Service Quality Management, Service Cost and Loyalty from the Standpoint of Bangladesh - Chakraborty, Brishti; Goswami, Uzzal (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2023)
The objective of this study is to assess the relationship between service quality, service costs, and patient loyalty. This study also tries to find out a mediating effect of patient satisfaction between the quality of service and patient loyalty. Based on the literature, we have developed a proposed model and tested this model. Data was gathered using online media from 247 respondents. To analyze data the partial least square (PLS) method was used to find reliability, validity and statistical power. Findings reveal that service quality has a significant positive impact on patient loyalty. Patient satisfaction also mediates the relationship between service quality and patient loyalty. The study also shows that service cost is positively related to service quality, patient satisfaction, and patient loyalty. The healthcare service quality aspects such as administration and the physical environment are positively associated with patient loyalty which is mediated through patient satisfaction. Other dimensions such as interaction, reactivity, and staff (p >0.05) have insignificant influence on service quality. Results depict that service quality inclines to create satisfaction and loyalty among patients. Findings indicate that authorities should employ efficient staff and maintain a strong financial structure to implement TQM practices more effectively.